1990
DOI: 10.1007/bf02184688
|View full text |Cite
|
Sign up to set email alerts
|

Neurovirulence of herpes simplex virus types 1 and 2 isolates in diseases of the central nervous system

Abstract: Herpes simplex virus (HSV) isolates derived from the central nervous system of ten patients with HSV-1-induced encephalitis, one patient with multiple sclerosis, and 14 patients with HSV-2-induced meningitis were investigated for neurovirulence by assaying the LD50 after nose and intracerebral (i.c.) inoculation of mice. HSV-1 encephalitis strains were significantly more virulent after nose inoculation (i.e. neuroinvasive) when compared with HSV-1 isolates from patients with oral lesions only, whereas HSV-2 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previously published studies on the sequence variability of the glycoprotein B and D genes did not reveal mutations specific for HSV-1 DNA sequences amplified from cerebrospinal fluid samples from encephalitis patients (40,44). However, different reports have shown that clinical HSV-1 isolates differ in virulence when tested in animal models (3,11,37). Recently, Mao and Rosenthal (23) reported that neuroinvasiveness properties of different HSV-1 strains derived from different organs of a neonate were associated with genetic alterations, including tandem repeats within the ICP34.5 gene.…”
Section: Discussionmentioning
confidence: 96%
“…Previously published studies on the sequence variability of the glycoprotein B and D genes did not reveal mutations specific for HSV-1 DNA sequences amplified from cerebrospinal fluid samples from encephalitis patients (40,44). However, different reports have shown that clinical HSV-1 isolates differ in virulence when tested in animal models (3,11,37). Recently, Mao and Rosenthal (23) reported that neuroinvasiveness properties of different HSV-1 strains derived from different organs of a neonate were associated with genetic alterations, including tandem repeats within the ICP34.5 gene.…”
Section: Discussionmentioning
confidence: 96%
“…HSV1 binds to heparan sulphate proteoglycan (HSPG) molecules on the cell surface,15 as do apoEs,16 the second subsequently entering cells via the receptors of the low density lipoprotein receptor (LDLR) family, which includes LDLR and LDLR related protein (LRP). Based on the fact that the affinity of apoE2 is lower than that of the other isoforms for these receptors,17 and on the suggestion that rare HSV1 mutants (highly neurovirulent) cause HSE,18 we speculate that if such mutants were to access cells via one of these LDLR family receptors instead of HSPG, they would compete with apoEs; apoE2 would compete to a lesser extent—hence allowing more entry and spread of virus. In Alzheimer's disease, we have proposed that apoEs and HSV1 compete for binding to HSPG molecules in the cell surface,3 4 apoE4 doing so less efficiently— thus allowing more virus spread—as its entry via HSPG is known to be less (in neuronal cells) than that of the other isoforms 16…”
Section: Discussionmentioning
confidence: 98%
“…However, it has recently been suggested that exogenous reinfection of HSV-1 contributes to the emergence of new variants through recombination (25). Therefore, a new HSV-1 variant would be able to gradually replace other HSV-1 viruses existing in a human population when a new mutant or variant of HSV-1 differs in virulence-related properties, as shown previously (1,7,32), and acquire the advantage of certain altered biological properties over other HSV-1 strains. An increase in the frequency of recurrence or in the efficiency of transmission would enable the emergence of such an HSV-1 replacement.…”
Section: Discussionmentioning
confidence: 99%